(untitled) (Lundiana: International Journal of Biodiversity, 2020)
Habitat modification has been pointed as one of the main causes of population decline and extinction of several species. Studies on communities in disturbed areas are very important for they provide data about the new organization of assemblages, imposed by the intense modification of habitats. An amphibian assemblage (Anura) was studied in an urban area under strong human pressure, 35 km southeast of Belo Horizonte (Minas Gerais state). Data collection was performed between March/2002 and March/2003, totaling 22 nights of observations. Fourteen species from three families were detected: Bufonidae (1), Leptodactylidae (5) and Hylidae (8). Most species, as well as the largest number of individuals, were recorded during the warm wet months of the year. Habitat use was quite restricted among species, unlike use of substrates. High substrate overlap was observed among hylids, which, besides sharing many types of substrate, occupied the same heights of the vegetation. The largest number of species was recorded on the vegetation at the margins of ponds, considered as the most important substrate for local anurans. Reproductive evidence was recorded for four species. The beginning of the reproductive period of Physalaemus cuvieri and Hyla faber was associated with the beginning of the rainy season, while Bufo crucifer and Scinax longilineus reproduced mostly during the dry months. The variety of habitats occupied and the local species richness, compared to other studies in the region, suggest that the study area, although greatly modified, may be of importance as an ecological corridor.